SPATIAL PATTERN OF URBAN HEAT SIGNATURE AND ITS IMPACT ON PAMOYANAN VILLAGE, CIANJUR DISTRICT - Sunukanto, V S; Semedi, Jarot Mulyo; Ash Shidiq, Iqbal Putut; Kamarudin, Norizah; Wibowo, Adi (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
According to the World Bank's Climate Change Knowledge Portal in 2020, the increase in annual temperature in Indonesia, which tends to rise by 0.3°C, is consistent with the Urban Heat phenomenon. Population growth and shifting land cover contribute to annual temperature fluctuations by reducing the amount of vegetated land. The increase in temperature in the urban environment has particular impacts on the community in terms of environmental changes. The term "Urban Heat Signature" refers to land cover in a localized urban environment with natural consequences due to solar radiation and high-low temperature values. This study was conducted in Pamoyanan Village, Cianjur District, by analyzing Land Surface Temperature images derived from Landsat OLI TIRS images, collecting air temperature measurements, and spreading field surveys about human perceptions. According to the processing results, the maximum temperature is greater than 30°C. The air temperature ranges from a maximum of 34.8°C in open land to a minimum of 27.4°C in medium vegetation. If this is the case, then the perception of human temperature significantly impacts comfort and the growing tendency for people to sweat in society.